Establishing Shipping Service Complex Standard Framework: Experience from Shanghai - Ge, Jiawei; Wang, Xuefeng; Wu, Pengcheng; Huang, Tianrong; Jiang, Huixian (International Journal of Management and Sustainability, 2018)
This paper introduced the experience of Shanghai in building the waterfront urban complex with industrial characteristics. In order to ensure the logic and scientific rationality, this paper developed the standard system on the concept of system engineering, based on which a three-dimensional space was proposed for the Shanghai Shipping Service Complex (SSC). Fundamental elements such as technology, management, economy and environment are analyzed and further classified, thus ensuring the systematicness and scientificity of the standard. The framework of standard system was then established through further elaborating the initial structure with four aspects as shipping service, building technology, environment friendly and sustainable management.